Molecular Detection of Human Parvovirus B19 (B19V) in an HIV-Infected Patient without AIDS, in Manaus, Amazonas, Brazil - Pinto de Figueiredo, Regina Maria; Alho da Silva, Luís Felipe (Journal of Health & Biological Sciences, 2025)
Human Parvovirus B19 (B19V) infection in asymptomatic Human Immunodeficiency Virus (HIV) patients often presents as an exanthematous illness with joint pain, potentially leading to the misdiagnosis as dengue or other diseases. This study presents a case of B19V/HIV co-infection in a patient initially suspected of having dengue who was undergoing treatment at a reference hospital in Manaus, Amazonas. The sample was tested for HIV and dengue virus and then stored at -80°C. HIV-positive and dengue-negative, with B19V DNA recently detected. B19V should be included in the differential diagnosis, especially in regions prone to infectious agents that present similar clinical manifestations.